The Analysis of Figurative Language on Passenger Song Lyric in Runaway Album - I Putu Yoga Jelantik Palguna; I Wayan Juniartha; Komang Dian Puspita Candra (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2021)
This study is aimed to find out the types of figurative language in Passenger’s song lyric in Runaway album, and to analyze the meaning of figurative language in Passenger’s song lyric in Runaway album. The writer used the theory from Arp & Perrine (1991) to identify the types of figurative language and the theory from Leech (1981) to analyze the meaning of figurative language. The result of this study showed that are 6 types of figurative language found in Passenger’s song lyric in Runaway album. There is personification, metaphor, imagery, simile, symbol, and overstatement. The writer found simile is 9 data or 30%, the second types of figurative language is metaphor with total of number 6 data or 20%, imagery category with 3 data or 10%, there is also personification with 4 data or 13.3%, symbol category with 4 data or 13.3%, and the last on is overstatement with 4 data or 13.3%.